Mobile Banking - No Wires, No Worries - Pant, Kamal (Journal of Commerce and Trade, 2012)
M-banking is one of the newest approaches to the provision of financial services through information communication technology. It has increased its significance during the last decades and its importance is still continuing to increase. It enables payments to be transacted regardless of place and times, without purchasing internet. In the present study, an effort is made to know whether mobile banking services is depended on different age groups customers of SBI, in Uttarakhand, India with the help of statistical tool. An interesting finding, i.e., mobile banking services and age groups are independent and free from biasness. In general, we can conclude from the results that the mobile banking services can play a useful role in our financial transactions.